A Study to Assess the Obesity and Its Determinants Among School Going Adolescents in Hyderabad - Shaik, Riyaz Shaik; Ahmad, Sultan Rizwan; Addepalli, Chandrasekhar (National Journal of Community Medicine, 2016)
Background: Obesity, once considered a problem of developed countries, is now growing enormously in many developing countries also. Changes in diet and physical activity raise the prevalence of obesity in children. Methodology: A cross sectional study was conducted among students of standard VIII – X in Hyderabad. Schools were selected from list of schools randomly. Total 763 children were included in study. Pre-tested questionnaires were used to collect information. The data was analyzed by using appropriate statistical tests. Results: In present study 49.02% were boys and 50.98% were girls. Majority of children belong to 13 years age group, and class-2 socio economic standard. About 58% of study population are from government school. Prevalence of obesity was 3.5% and it is more among girls and class-I socio economic status. There is significant association between obesity and excess calories intake, bakery and fatty food consumption, lack of physical activity, sedentary life style and family history. Conclusion: It was concluded that main modifiable risk factors of obesity among school going children were junk food and sedentary life style.